Implications of Constitutional Court Decision No. 46/PUU-VIII/2010 on the Rights of Children from Marriage Series Islamic Family Law Perspective - Achmad Hasan Basri (Kitabaca : Journal of Islamic Studies, 2024)
With the issuance of the decision of MK 46 / PUU-VIII / 2010 related to judicial review of article 43 paragraph (1) of the Marriage Law, that children born out of wedlock only have civil relations with their mothers and families. This caused pros and cons among the community, followed by the Fatwa of the Indonesian Ulema Council (MUI) Number 11 of 2012 concerning the Accusation of Children Resulting from Zina and Treatment of Him. Therefore, the author is interested in conducting a more in-depth analysis of how the impact of the Constitutional Court decision on the rules or norms relating to the inheritance rights of children from serial marriage in the legal order in Indonesia, as well as how the status of inheritance rights of children resulting from serial marriage according to the compilation of Islamic law. Design/methodology/approach - The method used by this study is in the form of normative legal review using a legal regulatory approach that examines a norm rule and a linear case approach with the issue to be solved. Research limitations/implications – This paper aims to examine more deeply the implications of the Constitutional Court decision No. 46/PUU-VIII/2010 on the legal order in Indonesia, more specifically the issue of children's rights. Findings – The issuance of Constitutional Court Decision No. 46/PUU-VIII/2010 has implications for the order of marriage norms in Indonesia, especially regarding the position of children from serial marriages. The Constitutional Court formulated a new norm, that children born out of wedlock have ties not only to their mother but also to their biological father. Especially for those who perform istbat marriages or determine the offspring of children, which have been legalized through the decision of the Religious Court get recognition from the state and the rights inherent in it as heirs of their biological father. The norms of inheritance fiqh, which are based on the idea that if the marriage is valid, then the child of that marriage is also valid and has the status of the father's heir. Originality/value – In the above review, it has not been examined regarding the impact of the issuance of the Constitutional Court decision on the legal order in Indonesia, specifically the issue of inheritance rights and other rights that can be obtained from his biological father..